Case Report: Practical approach to unmask unspecific adverse effects under lipid-lowering medication - Büttner, Thomas; Hartmann, Gunther; Coenen, Martin (Frontiers in Cardiovascular Medicine, 2025)
The nocebo effect, driven by negative expectations rather than pharmacological mechanisms, contributes significantly to medication non-adherence, particularly in lipid-lowering therapy. Up to 50% of reported statin-related adverse effects may result from nocebo responses, leading to unnecessary discontinuation and increased cardiovascular risk. Blinded provocation tests may offer a solution for the differentiation of true drug intolerance from nocebo-driven symptoms. Although this methodology is well-established in experimental studies, it has not been transferred to routine clinical practice so far. We present a 65-year-old female with hypercholesterolemia and cardiovascular risk factors who experienced recurrent, dose-dependent left-sided lower abdominal pain with different lipid-lowering drugs. These symptoms prompted repeated and ultimately continuous treatment discontinuations, each followed by resolution of complaints. Despite extensive evaluations, no organic cause was found. To assess the role of nocebo effects, a six-week single-blinded, placebo-controlled crossover provocation test with a commercially available placebo preparation and atorvastatin placed in neutral pill containers was conducted. Upon initiation of the provocation phase, the patient experienced similar intermittent symptoms under both treatments. The pain ratings on a numeric rating scale did not significantly differ during placebo (mean: 2.75) and atorvastatin administration (mean: 3.26), suggesting that these symptoms were not pharmacologically induced. Following information of the patient, atorvastatin therapy could be continued. During continued intake over several weeks, symptoms further diminished, reinforcing the therapeutic value of addressing nocebo effects. This case report provides for the first time the structured and detailed step-by-step description of a pragmatic approach for a prospective blinded, placebo-controlled provocation testing that can directly be implemented in routine clinical practice. This method enables the distinction of true drug intolerance from nocebo effects, thereby enabling necessary therapies and highlighting its diagnostic and therapeutic potential.